Comparative Evaluation of Surgical Procedures with Clinical Equipoise: The Unique Perspective of Our Hand Therapy Colleagues. Issue 1 (February 2018) - Schreiber, Joseph J.; Clark, Susan; Yao, Jeffrey
Background: There are several accepted surgical treatment options available for carpal tunnel syndrome, thumb carpometacarpal joint (CMC), osteoarthritis (OA), and wrist degenerative joint disease. Questions/Purposes: We sought to obtain the views and preferences from a cohort of certified hand therapists (CHT) and hypothesized that this source may identify differences in procedures that are otherwise widely believed to have clinical equipoise. Methods: Five hundred twelve CHTs were surveyed regarding their experience, volume, and referral base along with their subjective assessments and preferences regarding open versus endoscopic carpal tunnel release (CTR), various surgical procedures for CMC OA, and proximal row carpectomy (PRC) versus 4-corner fusion (4-CF). Results: The average CHT surveyed had 15.2 years experience and had a referral base of 7.7 different hand surgeons. Twenty-seven percent of respondents perceived superior pain control and incisional tenderness following open CTR compared to that of endoscopic CTR. However, 68% of CHTs would elect to undergo an open CTR themselves. There was no clear consensus for the optimal reconstructive technique for thumb CMC OA. As compared to that of 4-CF, PRC was thought to result in superior pain control (34 versus 22%), motion (43 versus 18%), and earlier discharge from therapy (32 versus 19%); however, 53% of respondents would prefer a 4-CF for themselves. Conclusions: Hand therapists are intimately involved in the care of surgical patients and provide an educated and unique source for evaluating postoperative outcomes.